2001
DOI: 10.1359/jbmr.2001.16.12.2339
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Transforming Growth Factor β in Chondrocytes Undergoing Endochondral Ossification

Abstract: Transforming growth factor ␤ (TGF-␤) has well-documented roles in chondrocyte maturation and endochondral ossification, but the mechanisms of TGF-␤ activation during these processes remain unclear. In this study, we analyzed TGF-␤ activation in chick embryo resting, proliferating, and hypertrophic chondrocytes in culture. We found that both levels and activation of TGF-␤ increased substantially with maturation. The majority of TGF-␤ produced by resting cells over culture time remained latent, but a larger port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 60 publications
(194 reference statements)
0
46
0
Order By: Relevance
“…Extracellular matrix-bound TGF␤ are normally stored in latent forms and can be released and activated by various serine proteases and MMPs, including MMP-9 and MMP-13 (30,31). We found that ACLtransected OA joints released elevated amounts of active TGF␤ in organ cultures, while ALN treatment suppressed the release of TGF␤ toward control levels.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Extracellular matrix-bound TGF␤ are normally stored in latent forms and can be released and activated by various serine proteases and MMPs, including MMP-9 and MMP-13 (30,31). We found that ACLtransected OA joints released elevated amounts of active TGF␤ in organ cultures, while ALN treatment suppressed the release of TGF␤ toward control levels.…”
Section: Discussionmentioning
confidence: 74%
“…In the medial tibial plateaus from ACL-transected joints, loss of proteoglycan was observed at 2 weeks postsurgery (Figures 8a and 9a). Two metalloproteinases, MMP-9 and MMP-13, have been implicated in the proteolytic activation of latent TGF␤ in cartilage tissue (29)(30)(31). As shown in Figure 8, activated TGF␤ (blue) was found in the proximity of MMP-9 (brown) (Figure 8b) in the articular cartilage of ACL-transected joints.…”
Section: Aln Blocking Of the Recruitment Of Trappositive Cells To Ostmentioning
confidence: 99%
“…TGF-beta also has welldocumented roles in chondrocyte maturation and endochondral ossification [14]. Autocrine and paracrine stimulation by TGF-b is important in the maintenance and expansion of the mesenchymal stem/progenitor cells, the progenitors of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-PI is a potential chemotactic stimulator for bone cells and promotes biosynthesis of extracellular matrix [30]. This growth factor actively regulated chondrogenesis and osteogenesis in bone regeneration [6,9,45]. The results of RT-PCR and immuno-histochemistry demonstrated that TGF-PI expression was elevated after ESW treatment.…”
Section: Discussionmentioning
confidence: 99%